Perbedaan Tingkat Stres Kerja Antara Shift Pagi, Sore Dan Malam Pada Perawat Rawat Inap Di Rumah Sakit Umum Daerah Banyudono Boyolali - Ikrimadhani, Tazkia; , Tarwaka, PGDip Sc, M.Erg; , Kusuma Estu Werdani, SKM., M.Kes (2015)
Shift work is the arrangement of working hours by a workplace to do something that is usually divided into work in the morning, evening and night. Occupational stress is emotional and physical response that is distracting or detrimental to that occur when the demands of the task do not match with the capabilities, resource or desire of workers. This study aim to know the difference between the levels of occupational stress shift in the morning, evening and night on Inpatient nurses in RSUD Banyudono Boyolali. This study uses analiytic observational method with crosssectional approach. The population in this study are all nurses of inpatient room in the hospital Banyudono Boyolali which is totally 38 nurses. Sampling technique uses total sampling. Using the Kruskal-Wallis analysis indicates that there are significant differences between level of occupational stress shift in the morning, evening and night on Inpatient nurses in RSUD Banyudono Boyolali with p value = 0,036 on highest stress levels at night shift , meanwhile the value of the mean rank is 66,91. It is recommended the improvement of the management of working hours such as adding working hours on the afternoon shift only 6 hours in order to the nurses on night shift was not just for 11,5 hours.